Upstream color - Seimetz, Amy 1981-; Sensenig, Andrew 20. Jh (New Video Group, 2013)
"A man and woman are drawn together, entangled in the life cycle of an ageless organism. Identity becomes an illusion as they struggle to assemble the loose fragments of wrecked lives." [IMDb.com]
Orig.: USA 2013